2005
DOI: 10.1093/cercor/bhi098
|View full text |Cite
|
Sign up to set email alerts
|

Layer 6 Cortico-thalamic Pyramidal Cells Preferentially Innervate Interneurons and Generate Facilitating EPSPs

Abstract: The properties of the connections made by the axons of pyramidal cells with cortico-thalamic (CT)-like morphology with a range of postsynaptic layer 6 targets were studied with dual intracellular recordings in slices of adult rat and cat neocortex. The cells were filled with biocytin and identified morphologically and, where appropriate, immunofluorescently. CT-like pyramids contacted interneurons with a very high probability (up to 1:2) but contacted other layer 6 pyramidal cells only rarely (approximately 1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
94
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 22 publications
15
94
1
Order By: Relevance
“…The mean membrane properties of layer VI pyramidal neurons recorded (n ϭ 325) were 92 Ϯ 1 mV spike amplitude, 240 Ϯ 11 M⍀ input resistance, and Ϫ78 Ϯ 1 mV resting potential. Because corticothalamic neurons are suggested to send a collateral axon to local circuit interneurons (West et al, 2006), we also collected data from layer VI fast-spiking interneurons. These cells were patched based on their small, circular morphology and were confirmed electrophysiologically by their characteristic, fast spiking pattern on injection of depolarizing current pulses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean membrane properties of layer VI pyramidal neurons recorded (n ϭ 325) were 92 Ϯ 1 mV spike amplitude, 240 Ϯ 11 M⍀ input resistance, and Ϫ78 Ϯ 1 mV resting potential. Because corticothalamic neurons are suggested to send a collateral axon to local circuit interneurons (West et al, 2006), we also collected data from layer VI fast-spiking interneurons. These cells were patched based on their small, circular morphology and were confirmed electrophysiologically by their characteristic, fast spiking pattern on injection of depolarizing current pulses.…”
Section: Methodsmentioning
confidence: 99%
“…Our preliminary analysis suggested that the firing properties of the layer VI pyramidal neurons in rat could be a useful criterion to predict which neurons were likely to have nicotinic currents, as shown in Figure 2. Recent work has suggested that corticothalamic layer VI neurons are regular spiking neurons (West et al, 2006), whereas layer VI corticocortical neurons tend to be burst-spiking neurons (Mercer et al, 2005). Therefore, we compared nicotinic inward currents between regular spiking and bursting neurons from rats from ages P15 to P42.…”
Section: Nicotinic Currents In Layer VI Pyramidal Neurons Change Acromentioning
confidence: 99%
See 1 more Smart Citation
“…Infragranular pyramidal cells, including putative CTNs, make facilitating synaptic connections on nearby interneurons (32,33). To rule out that antidromically activated CTN axon collaterals contributed to the facilitating EPSPs in layer 5 SOMϩ interneurons, we recorded from infragranular, ''regular-spiking'' (Fig.…”
Section: Latencies Of Antidromically Evoked Spikes In Corticothalamicmentioning
confidence: 99%
“…There are at least three common inter-spike intervaldependent measures of the short-term synaptic depression: Paired Pulse Ratio (PPR) as in (Gompf and Allen, 2004), Paired Pulse Depression (PPD) as in (Bannister and Thomson, 2007) and II-PSP-Integral to I-PSP-Integral ratio as in (Thomson, 1997). One can also mention consecutive postsynaptic responses to dual presynaptic stimulation, e.g (Baldelli et al, 2007) (PSC) and (West et al, 2006)(PSP), or steady state PSC amplitude (Sun et al, 2005) .…”
Section: Measures Of Short-term Synaptic Depressionmentioning
confidence: 99%